A Study Of Prevalance Of Altered Joint Proprioception Of Ankle Joint In Competative Roller-Skating Players - jadhav , Sakshi; Doijad, Amruta; Pathan, Umiya I. (Journal of Neonatal Surgery, 2025)
background proprioception is defined as one’s ability to integrate the sensory signals from various mechanoreceptors to thereby determine body position and movement in space and plays important role in balance control. ankle proprioception can be affected by sports specific training, sports related injuries and fatigue which lead to altered balance ability. overall, the studying ankle proprioception in skating players provides a valuable insight into injury prevention, performance optimization, rehabilitation strategies and equipment design contributing to the overall wellbeing and success of athletes in sports. methods and materials this cross-sectional study was conducted at three sports academies over 1.5 years. 60 roller skating players recruited for this study altered joint proprioception of ankle joint. pre and post assessments were conducted to measure change in proprioception using goniometer and functional capacity of ankle joint measured by foot ankle ability measuring scale. result the analysis revealed prevalence of altered joint proprioception of ankle joint in competitive roller-skating players. that means adolescent roller-skating players which significantly showed a difference in their proprioception of ankle joint. out of 60 participants 54 were positive for altered joint proprioception and 6 were negative with that showed 90.00% prevalence of altered joint proprioception of ankle joint in competitive roller-skating players. with reduced range of motion (rom)closed eyes, which significantly showed a difference in their proprioception. difference was as follows with mean and sd: plantarflexion of rt is 43.77± 4.0, for lt43.45± 4.15. dorsiflexion rt11.58 ± 2.70 for lt is 11.67± 2.80. inversion rt leg is 26.02± 2.9 for lt is 26.67 ± 2.55. eversion rt leg is 14.72 ± 4.00 for lt is 14.80 ± 3.55. total participants were 60. total 49 participants were shows normal function of ankle joint with 81.67%. and 11 participants shows 18.33 nearly normal function with foot ankle ability measure scale conclusion this study concludes that prevalence of altered joint proprioception of ankle joint in competitive roller-skating players is 90.00%. with reduced range of motion of ankle joint that highlighted the functional impact on the performance of the athletes.